Home is where the bodies are - Rose, Jeneva (Ashland, OR : Blackstone Publishing, 2024)
"After their mother passes, three estranged siblings reunite to sort out her estate. Beth, the oldest, never left home. She stayed with her mom, caring for her until the very end. Nicole, the middle child, has been kept at arm's length due to her ongoing battle with a serious drug addiction. Michael, the youngest, lives out of state and hasn't been back to their small Wisconsin town since their father ran out on them seven years before. While going through their parents' belongings, the siblings stumble upon a collection of home videos and decide to revisit those happier memories. However, the nostalgia is cut short when one of the VHS tapes reveals a night back in 1999 that none of them have any recollection of. On screen, their father appears covered in blood. What follows is a dead body and a pact between their parents to get rid of it, before the video abruptly ends. Beth, Nicole, and Michael must now decide whether to leave the past in the past or uncover the dark secret their mother took to her grave"--
Keywords: Mothers -- Death -- Fiction; Siblings -- Fiction; Video tapes -- Fiction; Family secrets -- Fiction; Thrillers (Fiction); Novels; Romans